(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The difficult socio-economic conditions during post-independence period and continual emigration have had a direct impact on the reproduction of population in the RA. General analysis of population reproduction of the RA during post 1990s period is given in the article. Reproduction tendencies during 2010-2018, revealation of territorial differences and pointing current problems are especially highlighted.